The - Jerrold Levinson (Oxford University Press, 2003)
The Oxford Handbook of Aesthetics brings the authority, liveliness, and multi-disciplinary scope of the Handbook series to a fascinating theme in philosophy and the arts. Jerrold Levinson has assembled a hugely impressive range of talent to contribute 48 brand-new essays, making this the most comprehensive guide available to the theory, application, history, and future of the field. This Handbook will be invaluable to academics and students across philosophy and all branches of the arts, both as the reference work of choice and as a stimulus to new research and creativity